PEMBEBANAN NAFKAH IDDAH DAN MUT’AH PADA PERKARA CERAI GUGAT DENGAN PUTUSAN VERSTEK (Analisis Putusan PA. Sei Rampah No: 991/Pdt.G/2022/PA.Srh) - Ramadi, Bagus; Ramadi, Bagus (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2022)
Divorce is the breaking up of a legal relationship, also known as talak. In Islamic civil law literature (fiqh) in Indonesia, divorce can be filed by the husband (cerai talak) and divorce can also be filed by the wife (cerai gugat). The divorce proposed by the husband in the fiqh literature is called talak, while it is called the divorce proposed by the khuluk wife (ransom divorce) with the wife's obligation to pay 'iwadh. Between divorce by way of talak and divorce by way of khuluk husband or ex-husband has different obligations as regulated in the Compilation of Islamic Law. This study was conducted to find out the judge's legal considerations regarding the imposition of Iddah and mut'ah living expenses in divorce cases with verstek decisions and their relevance to the imposition of Iddah and mut'ah living expenses in litigation divorce cases. 991/PDT.G/2022/PA.Srh. in terms of the Compilation of Islamic Law. This research is a qualitative research with an empirical juridical approach. The primary data in this study is the decision of the Sei Rampah Religious Court No. 991/PDT.G/2022/PA and secondary data in this study include the Marriage Law, the Compilation of Islamic Law, books, journals and relevant previous research. The data analysis method of this research is descriptive analytical with a deductive pattern. The data collection instrument is the document study method on the decision no. 991/PDT.G/2022/PA.Srh. and interviews. The results showed that the judge's main considerations based on SEMA No. 3 of 2018 concerning the implementation of the formulation of the results of the 2018 Supreme Court Chamber Plenary Meeting as a Guide to the Implementation of Duties for the Court. The legal formulation of the Religious Chamber stated that the wife in a divorce case can be given mut'ah and 'iddah maintenance as long as it is not proven nusyuz.  Keywords: Iddah, Mut'ah, Divorce, Verstek Decision